Potential interactions between syntrophic bacteria and methanogens via type IV pili and quorum-sensing systems. (May 2020) - Yin, Qidong; Gu, Mengqi; Hermanowicz, Slawomir W.; Hu, Hongying; Wu, Guangxue
Graphical abstract: Highlights: This study clarified the co-occurrence network of syntrophs and methanogens. Diverse quorum sensing genes were detected in all anaerobic sludge samples. Two quorum sensing signals are suggested to impact the regulation of type IV pili. Environmental factors significantly affected the syntrophic patterns. Abstract: Interspecies electron transfer plays an important role in syntrophic methanogenesis. Direct interspecies electron transfer (DIET) between syntrophic oxidizers and methanogens via conductive pili has been only confirmed in some specific co-cultures. This study examined potential syntrophic cooperation via type IV pili and quorum sensing between widespread syntrophic bacteria and methanogens through a metagenomic analysis of 12 anaerobic sludge samples. We found that Methanosaeta and Methanosarcina, which are reported to have DIET ability, were dominant in most methanogenic samples. Putative conductive pili genes were found in some typical syntrophic bacteria, which has rarely been reported previously. The existence of diverse quorum-sensing genes suggested that various quorum-sensing systems might participate in the communication of anaerobic microorganisms. Specifically, the diffusible signal factor and 3′-5′ cyclic diguanosine monophosphate related genes were mainly assigned to syntrophic bacteria. These results suggest that the combined regulation of these signals might be responsible for the biosynthesis of type IV pili and affect syntrophic interaction during methanogenesis. These novel results provide fresh evidence to support the widespread existence of DIET in anaerobic methanogenic systems; therefore, regulating the quorum-sensing system may promote syntrophic interaction.